The influence of product quality on purchase interest with halal awareness as an intervening variable - Nofrida, Desi; Mesta, Hendri Andi (Marketing Management Studies, 2023)
The purpose of this study is to find out and analyze the extent to which the influence of product quality on purchasing interest with halal awareness as an intervening variable in "Aak Ramen Yuk". The population in this study is the people of Lubuk Basung, Agam regency with a purposive sampling of 200 respondents. Quantitative analysis techniques with the help of SPSS (Statistical Product and Service Solution) version 20 software in the form of path analysis and Sobel test as mediation tests. The research results obtained show (1) the direct influence of product quality on purchase interest, (2) the direct influence of the product quality variable on halal awareness, (3) the direct influence of the halal awareness variable on purchase interest, (4) indirect influence of the product quality variable on purchase interest from the results of the Sobel test.